Cofilin: a redox sensitive mediator of actin dynamics during T-cell activation and migration - Samstag, Yvonne; John, Isabel; Wabnitz, Guido H. (Immunological reviews, 2013)
Cofilin is an actin-binding protein that depolymerizes and/or severs actin filaments. This dual function of cofilin makes it one of the major regulators of actin dynamics important for T-cell activation and migration. The activity of cofilin is spatio-temporally regulated. Its main control mechanisms comprise a molecular toolbox of phospho-, phospholipid, and redox regulation. Phosphorylated cofilin is inactive and represents the dominant cofilin fraction in the cytoplasm of resting human T cells. A fraction of dephosphorylated cofilin is kept inactive at the plasma membrane by binding to phosphatidylinositol 4,5-bisphosphate. Costimulation via the T-cell receptor/CD3 complex (signal 1) together with accessory receptors (signal 2) or triggering through the chemokine SDF1α (stromal cell-derived factor 1α) induce Ras-dependent dephosphorylation of cofilin, which is important for immune synapse formation, T-cell activation, and T-cell migration. Recently, it became evident that cofilin is also highly sensitive for microenvironmental changes, particularly for alterations in the redox milieu. Cofilin is inactivated by oxidation, provoking T-cell hyporesponsiveness or necrotic-like programmed cell death. In contrast, in a reducing environment, even phosphatidylinositol 4,5-bisphosphate-bound cofilin becomes active, leading to actin dynamics in the vicinity of the plasma membrane. In addition to the well-established three signals for T-cell activation, this microenvironmental control of cofilin delivers a modulating signal for T-cell-dependent immune reactions. This fourth modulating signal highly impacts both initial T-cell activation and the effector phase of T-cell-mediated immune responses.